Aktivitas Ekonomi Berupa Investasi Mata Uang Digital Kripto Untuk Proses Perolehan Laba atau Keuntungan, Dalam Novel Moonbound Karya Jang Ryunjin - Made Wulan Febryani; Tegar Ridho Cahyo; Aghil Satrio Wicaksono; Eva Dwi Kurniawan (CV. ITTC INDONESIA, 2022)
This research will reveal how the field of accounting is related to a literary work in the form of a novel. The literary work that will be used as a research source is the novel entitled Moonbound by Jang Ryunjin. The method used in this research is descriptive qualitative which provides an in-depth and contextual description of economic activities related to digital cryptocurrency investment transactions. The research data used is text collected from various sources that are considered relevant to the research topic. The results obtained from this research can show how economic activities or transaction processes to gain profits from investing in crypto digital currency in the form of bitcoin/ethereum use a security system called blockchain.